How mothers with severe emotion dysregulation use DBT skills in parenting contexts: observational coding of skills use in a DBT skills training group - Yoel Everett; Olivia A. Frigoletto; Jacqueline R. O’Brien; Amy L. Byrd; Stephanie D. Stepp; Maureen Zalewski (Borderline Personality Disorder and Emotion Dysregulation)
Abstract Background Dialectical Behavior Therapy’s (DBT) well established effectiveness in reducing emotion dysregulation, and the growing recognition that parental emotion regulation is critical to effective parenting has led to increasing interest in the applicability of DBT skills to parenting. Efforts to integrate DBT and parenting interventions would benefit from an empirical examination of which DBT skills are most useful to parents with emotion dysregulation. Methods This study used clinician-rated observational coding of skill use examples that were provided by mothers with severe emotion dysregulation (n = 16) who participated in a standard 48-week DBT Skills Training (DBT-ST) program in the context of a larger randomized controlled trial (NCT03060902). Mothers described their use of DBT skills during the homework review portion of DBT-ST sessions and video-recordings were then examined and coded to identify which DBT skills mothers most frequently described using in parenting situations (vs. non-parenting situations) and which skills were used to either increase positive parenting behaviors or to decrease negative parenting behaviors. Results A total of 220 skill use examples were coded and approximately one-quarter described skill use in parenting situations. Mindfulness, Distress Tolerance, and Emotion Regulation skills were the most frequently described skills used in parenting situations, while Interpersonal Effectiveness skills were rarely coded. Mindfulness and Emotion Regulation skills were most often coded when mothers’ parenting goal was to increase positive parenting, while Distress Tolerance skills were most often coded when mothers’ parenting goal was to decrease negative parenting behaviors. Conclusions Results provide an empirical basis which clinicians and treatment developers can use when selecting DBT skills to apply towards parenting challenges.